Quality of life and factors associated with the practice of physical exercise in master's students of a public university in the central region of the country - Barbosa , Welistânia Vieira Bispo; Junior , Gilmar Jorge de Oliveira; Segri , Neuber José (Seven Editora, 2023)
Introduction: Physical exercise has been consolidating itself as a fundamentally important element for improving health and quality of life.  Objectives: To evaluate the quality of life and factors associated with performing physical exercises in master's students at a public university in the central region of Brazil.  Methodology: This is an observational, cross-sectional study, self-completed survey type, with data collection being carried out online, in a sample of 375 master's students who answered the Epworth Sleepiness Scale, SRQ-20 instruments, and WHOQOL-brief, in addition to questions related to sociodemographic characteristics and lifestyle. Multiple Poisson regression model with robust variance was used to verify associations. Results: Of the 375 participants, 57.34% claimed to perform physical exercise, which was associated with the variable's alcohol consumption, dissatisfaction with their health status, and the possibility of having a common mental disorder. Regarding the domains of quality of life, master's students who performed physical exercises obtained significantly better values. Conclusion: Performing physical exercises proved to be a great option to circumvent the sedentary routine experienced by master's students, bringing benefits to their health and quality of life. DOI:https://doi.org/10.56238/alookdevelopv1-025